Social representations about old age in public health policies that involve corporal practices with older adults. A study of the National Hadob program and Active Health program (Impetus, 2021)
Aging and old age consist of processes gradual in the life of the subjects. In turn, these subjects make up an ever-expanding demographic universe and heterogeneous. In the studies in this regard, confusion abounds between scientific data and representations of old age present in the popular imagination. Between these two positions are observed opposing: positive social representations and negative social representations. In this presentation the speeches are analyzed from of which public policies have been designed in the health area. These have involved in its implementation corporal practices with older adults; their arguments and guidelines reflect a representation particular of old age. Upon studying them, social dimensions, through which they organized categories of analysis, to recognize some aspects for their interpretation and analysis. Through a qualitative research approach, the obtained preliminary advances, which are not intended universalize the knowledge acquired as if it were of an absolute truth, but they try to offer a framework of understanding for certain characteristics of the studied reality. Finally, in the analysis of the speeches of these programs, a reductionist view of the bodily practices in old age. They represent the practices sports and ascetic habits as utilitarian goods for the achievement of a healthy longevity, and leave aside the subjective and collective meanings of which the older subjects who circulate through said scenarios.